Analisis Hukum Pembentukan Undang-undang dan Peraturan Daerah: Mengurai Isu Kualitas dan Konsistensi Regulasi Nasional - Farash Ayu Mayladani; Adinda Dwi Novalia; Tasya Yulieta Angelin; Akmal Alaric Jauhary Putra; Adrian Dimas Satriaji (VJJ, 2025)
This paper examines the development of national laws (UU) and regional regulations (Perda) in Indonesia, with particular attention paid to the formal framework, recurring quality issues, and emerging difficulties in the context of regional autonomy. The study examines relevant legislation, the drafting process, and actual experiences of national and regional lawmaking using a normative legal approach. The findings show that although the current legal framework for legislation is well-organized, problems including overlapping authority, uneven standards, and poor policy planning still exist. However, a lack of technical experience, capacity gaps across regional administrations, and local political influence all have an impact on the quality of Perda at the regional level. These issues highlight the need for a stronger national policy that improves planning standards. These problems provide tangible proof of the need for a more defined national strategy that raises planning standards, guarantees more uniformity in regulations, and continuously supports regional governments in passing sensible and useful legislation. Keywords: The Legislative Procedure; Standard Of Regulations; Coherence Of Policies.